(untitled) (Journal of Comparative & International Higher Education, 2022)
ABSTRACT It is contended that Lusophone universities are to a certain degree deprived access to American and European scholarships in the 21st century. We examine the validity of this statement, focusing on the barriers scholars often face when accessing scholarships using English. To explore the constraints English language imposes on Mozambican lecturers pursuing international scholarships, the study employed qualitative research methods using structured interviews. The sample of interviewees included university lecturers from Eduardo Mondlane University. The discussions of the study were guided by two dominant themes: language coloniality and academic oppression (Lack of accessibility). Participants had their unique experiences while attempting scholarship applications and this study also captured their challenges. Eighty percent of participants could not express themselves fluently in English and the researcher had to switch to Portuguese to get quality responses. The study contributes to International comparative higher education language policy development by presenting the impediments posed by the English language to Mozambican universities seeking European and American scholarships. Keywords: English language barrier, coloniality, oppression, European university, American university, scholarship, Mozambique